2017
DOI: 10.1007/s13304-017-0460-x
|View full text |Cite
|
Sign up to set email alerts
|

Review of surgical implant procedures for male incontinence after radical prostatectomy according to IDEAL framework

Abstract: Most aspects of surgical therapy for stress urinary incontinence (SUI) after radical prostatectomy (RP) are under debate or poorly studied. A systematic review was conducted and a literature search was carried out through PubMed database for articles on the surgical procedures for male SUI after RP published from Jan 2010 to Nov 2016. The efficacy results (pad count, 24 h pad test), complications, and quality of life (QoL) were reported. The included studies were categorized in accordance with the IDEAL framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Twenty review articles identified were systematic reviews and the remaining 15 were narrative reviews. Ten review articles used the IDEAL framework to categorize studies included within the review .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty review articles identified were systematic reviews and the remaining 15 were narrative reviews. Ten review articles used the IDEAL framework to categorize studies included within the review .…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have shown that anterior colporrhaphy, compared to posterior colporrhaphy, has higher rates of reoperation (20.2% vs 14.6%) 17 and complication (27% vs 20%). 18 This suggests that, relative to isolated posterior colporrhaphy, anterior or combined colporrhaphy procedures are more complex and have potentially higher complication rates and longer hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…Only very few studies are available on postprostatectomy incontinence. Stage 0-2 IDEAL studies were revealed by systematic review of the literature [32]. Heesakkers et al recently published a review on intraoperative surgical factors contributing to incontinence after surgery, which shows that the level of evidence of most trials is low [33].…”
Section: Discussionmentioning
confidence: 99%